(untitled) (Research, Society and Development, 2022)
Forests worldwide are essential goods for humanity as they provide support, provision, regulation, and cultural ecosystem services. In Brazil, the Atlantic Forest has lost much of its original cover, is currently represented by relatively small fragments in an anthropized matrix. Therefore, it is very relevant to analyze if forest fragments change in related the fragmentation of the original native vegetation and how they maintain their quality. This study aimed to analyze whether patch-level metrics are related to forest quality (biotic integrity) and whether relief features such as headboards are related to forest fragmentation patterns to provide subsidies for public planning and environmental conservation policies. The methodology involved mapping forest fragments (F) and drainage headboards (DH), calculating patch-level metrics (AREA, SHAPE, PROX), and the biotic integrity (BII) of the forest. Spearman’s Correlation Coefficient was used to test the relationship between variables. The results showed a significative robust relationship between AREA and BII and significative medium relationship between SHAPE and DH, confirming partially the initial assumptions of the research. We concluded that the integrity of the forest fragment and the presence of drainage headboards must be considered in public planning and environmental conservation policies.